Susceptibility Patterns of Multidrug-Resistant Acinetobacter Baumannii among, Intensive Care, Unit Patients - Israa H. Alfuaadi; Haneen H. Jawad; Ruaa L. Alabodi (Journal of Science in Medicine and Life, 2026)
Background: In intensive care units (ICUs), Acinetobacter baumannii is a prevalent cause of healthcare-associated infections, and antibiotic resistance significantly constrains treatment alternatives. The objectives of this study were to assess the antimicrobial susceptibility profiles of A. baumannii isolates from intensive care unit patients, determine the prevalence of extensively drug-resistant (XDR) and multidrug-resistant (MDR) phenotypes, and quantify the resistance burden across critical antibiotic classes. Methods: The results of antimicrobial susceptibility testing were analyzed following CLSI guidelines. Five types of antimicrobials were employed to evaluate resistance, and isolates were classified as multidrug-resistant (MDR) or extensively drug-resistant (XDR) according to standardized criteria. The resistance load of MDR and XDR isolates was analyzed, and mean resistance scores along with standard deviations were calculated. Findings: All primary classes of antibiotics exhibited elevated resistance rates, particularly towards carbapenems, fluoroquinolones, and cephalosporins. The majority of isolates were classified as XDR, indicating resistance to nearly all tested antibiotic classes. XDR isolates had consistently higher resistance scores than MDR isolates, signifying more advanced resistance profiles. Conclusion: Enhanced antibiotic stewardship, continuous resistance monitoring, and rigorous infection control protocols are urgently required, as demonstrated by the prevalence of XDR A. baumannii in intensive care units.